Improvement of Learning Outcomes in Pkn Learning Through Problem Based Learning Model with Audio Visual Media Class IV Students SD Negeri 41 Sabangko - Haslinda Haslinda (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Teachers still teach more and pursue targets that are oriented towards final exam scores. This relates to the formation of character, morals, attitudes and behavior of students who only want good values without being balanced with improvements in the character, morals, attitudes and behavior of the child. To improve the learning outcomes of Civics learning through the Problem Based Learning model using audiovisual media for grade IV SDN 41 Sabangko. This type of research is Classroom Action Research (PTK) through three learning cycles with data collection techniques, namely tests, observations, field notes, documentation, questionnaires and interviews. Data analysis, namely qualitative and quantitative analysis. The results showed that the three cycles carried out showed different values and the third cycle obtained better results so that the established hypothesis could be accepted as true, namely through problem-based learning with audiovisuals it could improve teacher skills, student activity, and student learning outcomes